Who uses and who benefits from warehouse receipt systems? An examination of contract level transactions on the Agricultural Commodity Exchange for Africa, 2011–2018 - Thunde, Jack; Baulch, Bob (International Food Policy Research Institute, 2020)
This paper examines who uses and who benefits from warehouse receipt systems using unique transaction level data from the Agricultural Commodity Exchange for Africa (ACE) based in Malawi. Between 2011 and 2018, the ACE warehouse receipt system was used 710 times, with most receipts issued for maize, pigeon peas and soybeans. Large traders took out both the largest number of warehouse receipts and deposited the largest volumes, followed by medium and small traders, farmers associations/groups, and then farmers. An inverse relationship exists between the duration of storage, the cost of financing and the returns that ACE warehouse receipt depositors make. Storing maize and soybeans for less than 180 days generally resulted in a depositor making a profit, while storing pigeon peas for less than 270 days, also generally resulted in profits to storers. However, 73 percent of warehouse receipts issued for pigeon peas made losses compared to 48 percent for maize and 53 percent for soybeans. Wide variations in profits to storers were linked to the collapse of pigeon pea exports and a fourfold de-cline in maize prices in 2016/17. This paper develops alternative storage rules with the aid of seasonal price patterns and analysis of depositors’ behavior. These rules suggest possible combinations of deposit and sale months that can be used to guide depositors within year storage decisions. The wider implications of the ACE experience for the development of warehouse receipt systems elsewhere in Africa are also discussed.